Serial cine-magnetic resonance imaging of left ventricular remodeling after myocardial infarction in rats. - Nahrendorf, M; Wiesmann, F; Hiller, K; Hu, K; Waller, C; Ruff, J; Lanz, T; Neubauer, S; Haase, A; Ertl, G; Bauer, W (2001)
The purpose of the present study was the serial investigation of morphological and functional changes after left coronary artery ligation in the intact rat using cine-magnetic resonance imaging (MRI). MRI studies were performed 4, 8, 12, and 16 weeks after myocardial infarction (MI) with an echocardiogram (ECG)-triggered cine-fast low-angle shot (FLASH)-sequence in a 7-Tesla magnet. MI-size, left ventricular (LV) mass and volumes, cardiac index, ejection fraction (EF), and remote wall and scar thickness of 11 Wistar rats were compared to four sham-operated rats. Stress MRI with dobutamine (10 microl/kg x minute) was performed at 16 weeks. In MI groups (small MI < 30%, N = 5, large MI > 30%, N = 6), there was significant increase of LV mass (small MI + 47.8% increase, large MI + 74.1%) and wall thickness (large MI 1.21 +/- 0.03 to 1.84 +/- 0.07 mm). Scar thickness declined from four to 16 weeks (large MI 0.92 +/- 0.06 to 0.38 +/- 0.02 mm, P < 0.05). End-diastolic volume of both MI groups was significantly elevated but increased further only in animals with large MI from four to 16 weeks (657.1 +/- 38.6 to 869.7 +/- 60.7 microL, P < 0.05). Compared to sham, EF was significantly depressed in MI (large MI 31.5 +/- 2.0%). Wall thickening declined from four to 16 weeks post-MI (large MI 50.9 +/- 9.9 to 28.9 +/- 4.4%, P < 0.05). During stress, sham and MI rats increased wall thickening from 66.5 +/- 8.2 to 111.2 +/- 6.7% and from 30.8 +/- 4.3 to 47.5 +/- 5.8%, respectively (P < 0.05). Hypertrophy was found in all animals with MI throughout the entire period of observation, whereas dilatation after four weeks was only detected in animals with large MI. These morphologic changes were accompanied by an early decline of EF; myocardial function characterized by wall thickening deteriorated later.